OPTIMALISASI PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI TOLERANSI ANTAR UMAT BERAGAMA PADA PESERTA DIDIK - Faisal, Awang; Setiawan, Agus (STAI Sangatta Kutai Timur, 2024)
This research aims to explore and identify optimal strategies and challenges faced by Islamic Education teachers in instilling the values ​​of inter-religious tolerance at SMP Negeri 1 Sangatta Selatan. Using a qualitative approach with a case study design, data was collected through in-depth interviews, classroom observations, and document analysis. The research results show that PAI teachers apply various effective teaching strategies, such as integrating the values ​​of tolerance in teaching materials, class discussions, and interfaith activities. The main challenges faced include stereotypes and prejudices embedded in students' minds, social pressure, and limited resources and teaching materials. Varying school and policy supports demonstrate the need for more consistent and adequate policy standards. Evaluation of the effectiveness of the method used shows a positive impact in increasing students' tolerance attitudes. This research emphasizes the importance of holistic support from various parties, including training and professional development for teachers, provision of supportive teaching materials, and consistent and inclusive policies. With a holistic approach and adequate support, tolerance education can become an integral part of the education system in Indonesia, contributing to the development of a peaceful and harmonious society.